La sobreprotección infantil en el desarrollo del lenguaje de los niños de inicial II, paralelo “B”, de la escuela de educación básica doctor Daniel Rodas Bustamante de la ciudad de Loja. Periodo lectivo 2017-2018 - Bravo Pardo, Erika Dayana (2018)
This research entitled: "Child overprotection in child development”: It has as general objective: To identify the factors that cause child overprotection and how it affects the development of language." The methods used to prepare this research work were: Deductive, Inductive, Synthetic Analytical, Descriptive, Statistical, these were used to describe and explain the research. The population consisted of 23 research subjects, distributed in 11 children, 1 teacher, 11 parents. The techniques and instruments that were applied were; data collection, direct observation, indirect observation, parents survey, interview with the teacher and then articulation cards were applied to evaluate the language development in the children of the initial parallel II "B" of the School of Basic Education Dr. Daniel Rodas Bustamante of the City of Loja. After the application of the methods, techniques and instruments, the following conclusion was reached: that most of the children are only children or the smallest within the family who give a result of spoiled children, the parents do not have a wide knowledge about how the overprotection influences In the development of the child, after having applied the articulation cards, it was possible demonstrate that 80% of children achieved an improvement in language articulation by optimizing previous results.